Characterization of a synthetic signal transduction system - Albrecht, Tessa, author; Medford, June, advisor; Bush, Daniel, committee member; Pilon-Smits, Elizabeth, committee member; Leach, Jan, committee member (Colorado State University. Libraries, 2012)
The Medford laboratory has developed a synthetic signal transduction system linking exogenous perception of a particular ligand to a transcriptional response. One application of this system is to produce plants that sense and respond to a specific ligand. The system was designed based on evolutionary conservation of histidine kinase signaling and uses bacterial components adapted to function in plants. The synthetic signaling system is responsive to extracellular ligand perception by a wild-type or modified ribose binding protein (RBP) scaffold. Upon ligand binding, RBP binds and activates a synthetic fusion histidine kinase made from the extracellular portion of the bacterial chemotactic receptor Trg and the cytoplasmic portion of the bacterial phosphate sensor PhoR. Activated Trg-PhoR transmits a phosphate signal to the bacterial response regulator PhoB. Upon phosphorylation PhoB translocates into the nucleus of a plant cell and activates transcription of the response gene(s). In addition to receiving a phosphate signal from Trg-PhoR, PhoB can be activated by exogenous cytokinin application suggesting that components of the cytokinin signaling pathway can interact with PhoB. Elimination or reduction of the interaction with cytokinin signaling components allows production of a more reliable signaling system. One goal of the following work was to reduce the interaction of PhoB with endogenous cytokinin signaling components. I attempted to identify a mutant form of PhoB that does not interact with cytokinin signaling components yet maintains function with the synthetic signaling system. I screened six different rationally selected PhoB mutants in plants for reduced response to exogenous cytokinin application. I concluded that a different approach will be needed to successfully reduce interaction with cytokinin signaling components. Another goal of this work was the identification cytokinin signaling components that interact with PhoB, possibly revealing a means to eliminate the interaction. I attempted to functionally express selected cytokinin signaling components in a bacterial testing system. After several failed cloning strategies, I conclude that the cytokinin sensor histidine kinase, AHK4, may be toxic and/or unstable in bacteria and expression of alternative genes will be needed to identify cytokinin signaling components that interact with PhoB. Additional work described here includes the independent testing of two computationally designed RBPs; one reported to bind the environmental pollutant methyl tert-butyl ether and the other reported to bind the explosive trinitrotoluene, for ligand dependent activation of the synthetic signaling system. These results show that the computationally designed RBPs do not function in a reliable manner and lead to the production of a detector plant using wild-type RBP to activate the synthetic signaling system that enables further analysis of the system components in plants.
Keywords: synthetic biology; histidine kinase signaling; synthetic signal transduction; PhoB; computational design